Determinants and consequences of the pharmacokinetics of rifampicin, isoniazid, pyrazinamide and ethambutol in a cohort of tuberculosis patients - McIlleron, Helen (Division of Clinical Pharmacology, 2014)
Includes bibliographical references (leaves 190-203).